Laser displacement measurement using intensity modulation with a phase-modulated radio-frequency signal. (15th December 2020) - Tanaka, Yosuke; Yamaguchi, Kyosuke; Yamamoto, Kenta; Yamada, Yoshiki
Abstract: We demonstrate a laser-based displacement measurement using an intensity modulator as a simple and wide-band intensity correlator. The proposed method applies intensity modulation not only to the output probe beam but also to the reflected beam from a target, where the fundamental frequency of modulation signal is the same for both, but the phase of modulation signal for the reflected beam is also modulated. The displacement is measured using harmonic signals from a photodetector. The principle is verified for 40 mm and 16 m ranges of displacement measurement, where the relative measurement uncertainty of 1.8 × 10 − 6 is achieved.